Exercise improves depression through positive modulation of brain-derived neurotrophic factor (BDNF). A review based on 100 manuscripts over 20 years - Jemni, Monèm; Zaman, Rashid; Carrick, Frederick Robert; Clarke, Neil David; Marina, Michel; Bottoms, Lindsay; Matharoo, Jagdeep Singh; Ramsbottom, Roger; Hoffman, Norman; Groves, Shad James; Gu, Yaodong; Konukman, Ferman (Frontiers in Physiology, 2023)
The aim of this review was to explore the relevant neurobiology and the association between peripheral levels of brain-derived neurotrophic factor (BDNF) and acute and short to long-term exercise regimes, as well as its relation to depression and antidepressant treatment. A 20-years literature search was conducted. The screening process resulted in 100 manuscripts. Antidepressants as well as acute exercise, particularly high-intensity, elevates BDNF in healthy humans and clinical populations, as evidenced from aerobic and resistance-based studies. Although exercise is increasingly recognised in the management of depression, acute and short-term exercise studies have failed to establish a relationship between the severity of depression and changes in peripheral BDNF. The latter rapidly returns to baseline, possibly indicating a quick re-uptake by the brain, aiding its neuroplasticity functions. The timescale of administration needed for the antidepressants to stimulate biochemical changes is longer than similar increases with acute exercise.